Performance of two Aspergillus IgG EIA assays compared with the precipitin test in chronic and allergic aspergillosis. (18th January 2013) - Baxter, C. G.; Denning, D. W.; Jones, A. M.; Todd, A.; Moore, C. B.; Richardson, M. D.
Abstract: Detection of Aspergillus IgG antibodies is important in the diagnosis of chronic pulmonary aspergillosis and allergic bronchopulmonary aspergillosis. Immunoprecipitation techniques to detect these antibodies appear to lack sensitivity and accurate quantitation compared with enzyme immunoassays (EIA). This study assessed the performance of two commercial EIAs compared with counterimmunoelectrophoresis (CIE). This was a prospective cohort study of 175 adult patients with chronic or allergic pulmonary aspergillosis. Aspergillus IgG antibodies were detected using CIE, Phadia ImmunoCap Aspergillus IgG and Bio‐Rad Platelia Aspergillus IgG. Inter‐assay reproducibility was determined for each method and 25 patients had two serum samples analysed within a 6‐month interval. When compared with CIE, both ImmunoCap and Platelia Aspergillus IgG had good sensitivity (97 and 93%, respectively) for detection of Aspergillus IgG antibodies. The level of agreement between the two EIAs for positive results was good, but the concentration of antibodies was not correlated between the tests or with CIE titre. ImmunoCap IgG inter‐assay coefficient of variation was 5%, whereas Platelia IgG was 33%. Median ImmunoCap IgG values for CPA and allergic aspergillosis were 95 and 32 mg/L, respectively, whereas Platelia IgG values were >80 and 6 AU/mL. The direction of CIE titre change over 6 months was mirrored by ImmunoCap IgG levels in 92% of patients, and by Platelia IgG in 72% of patients. Both ImmunoCap and Platelia Aspergillus IgG EIAs are sensitive measures of Aspergillus IgG antibodies compared with CIE. However, ImmunoCap appears to have better reproducibility and may be more suitable for monitoring patient disease.